2012
DOI: 10.1029/2011ja017291
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous ground‐satellite observations of meso‐scale auroral arc undulations

Abstract: [1] We present simultaneous ground-based and in situ measurements of a train of meso-scale (about 100-300 km) auroral arc undulations, occurring in the postmidnight sector ($1 MLT) between 0040 UT and 0054 UT on September 21, 2009. The undulations appeared at the auroral poleward boundary, and then moved eastward with a speed of 0.9-2.2 km s À1 . Dynamic behaviors of the associated meso-scale ionospheric plasma flows and current systems were also detected with the ground-based magnetometer and radar measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 40 publications
2
8
0
Order By: Relevance
“…Our work has demonstrated for the first time that as a macroscopic coherent process, the ideal MHD ballooning instability is capable of inducing the formation of plasmoids in the magnetotail configuration without relying on any microscopic, kinetic, or turbulent processes. In light of recent evidence found in ground and in situ observations for the presence of ballooning instability in the pre‐onset auroral and plasma sheet structures [ Saito et al , , ; Panov et al , ; Motoba et al , , ], our findings on the ballooning instability‐induced plasmoid formation may indeed provide a solid and practical scheme for ballooning instability in the near‐Earth magnetotail to play a critical role in triggering the substorm onset process.…”
Section: Summary and Discussionsupporting
confidence: 62%
“…Our work has demonstrated for the first time that as a macroscopic coherent process, the ideal MHD ballooning instability is capable of inducing the formation of plasmoids in the magnetotail configuration without relying on any microscopic, kinetic, or turbulent processes. In light of recent evidence found in ground and in situ observations for the presence of ballooning instability in the pre‐onset auroral and plasma sheet structures [ Saito et al , , ; Panov et al , ; Motoba et al , , ], our findings on the ballooning instability‐induced plasmoid formation may indeed provide a solid and practical scheme for ballooning instability in the near‐Earth magnetotail to play a critical role in triggering the substorm onset process.…”
Section: Summary and Discussionsupporting
confidence: 62%
“…The eastward propagation velocity along the orientation of the auroral form is estimated at 1,200 m/s. Similar eastward propagating auroral undulations were also reported by Motoba et al ().…”
Section: Event Studiessupporting
confidence: 90%
“…Azimuthally periodic auroral forms are commonly seen on equatorward arcs prior to substorm breakup [ Murphree et al , 1994 ; Elphinstone et al , 1995 ; Donovan et al , 2007 , 2008 ; Liang et al , 2008 ; Sakaguchi et al , 2009 ; Henderson , 2009 ; Rae et al , 2009a , 2009b ] and undulations in the poleward arc have been reported during a substorm recovery phase [ Motoba et al , 2012a ]. The equatorward arc forms are observed to brighten and expand prior to the auroral breakup, which has been associated with various instabilities in the inner magnetosphere [ Rae et al , 2010 ].…”
Section: Discussionmentioning
confidence: 99%